SALT LOADED HEAT PIPES: STEADY-STATE OPERATION AND RELATED HEAT AND MASS TRANSPORT - Simakin A.; Ghassemi A. (My University, 2003)
Fluids in the deep-seated zones (3.5–4.5 km) of active geothermal zones are known to have increased salinity and acidity that can enhance interaction with surrounding porous rocks. A possible mechanism for brine generation is the separation of the rising magmatic fluid into a gas-like and a liquid-like component. This work illustrates the main features of this mechanism by investigating the conditions for heat pipe convection of natural brines in hydrothermal systems. The well-established heat pipe regime for convection of two-phase pure water (vapor–liquid) in a porous column is extended to the case of boiling brines. In particular, the NaCl–H 2 O system is used to model the 1-D reactive flow with dissolution-precipitation in geothermal reservoirs. The quasi steady-state equations of the conservation of matter, Darcy’s law for the gas and liquid phases, and the heat balance equation have been examined while neglecting the temporal variation of porosity. A semi-analytical procedure is used to solve these equations for a two-phase fluid in equilibrium with a solid salt. The solution is in the form of the dependence of liquid volume fraction as a function of temperature for different heat fluxes. The solution is separated into two isolated regions by the temperature T =596°C, at the maximum fluid pressure for three-phase (H–L–V) equilibrium. In the case of unsaturated two-phase flow at the reference permeability of porous rocks (3·10 −16 m 2 ), the maximum heat flux that can be transferred through the porous column via convection is analytically estimated to be 4.3 W/m 2 . This is close to the corresponding value for the three-phase case that is numerically calculated to be 6 W/m 2 . Due to dissolution (partial leaching of oxide components by acid condensates) and precipitation of salt at the boiling front, heat transfer in a heat pipe in soluble media occurs in a direction opposite to the associated mass transfer. This can cause deep hydrothermal karsting that is manifested as surface subsidence at rates of about several cm/yr as observed in some active geothermal fields